(3GdEaUGM aj EYQGH GdcGajIs - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s ((3Ndjd Hf eUWai Hf MHjH s)
(3ChdgG (B:s
(3aj JCdjag ef bHd GdTjN GdaGVd hGdeQTO GdcGed aQjO GdYUQ HehLH GdETGQI GdePchQI s
(3BNQgG (B:s
(3hGdeaJhM eG bHdgG JbdH CdakG, hGdLedI NjQ GdeHJOC hGdCSejI GSJFfGa hbO Je eG aj gPG GdTQM ef GdcdGe s
(3HgG fXGe GdJYbjHIs
(3hHChdgG agQS ddehVhYGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
Keywords: (3GdfMhs